TEXNOLOGIK TARAQQIYOT VA GLOBALLASHUV JARAYONIDA YANGI QO‘SHMA SO‘ZLARNING SHAKLLANISHI - Karimova Nilufar Xabibullayevna (Web of Journals Publishing, 2025)
This article examines the emergence of new compound words in the French and Uzbek languages due to globalization, technological advancements, and social transformations. It analyzes how compound words are formed, their semantic changes, and their areas of application. The study highlights that most new French compounds originate from English, particularly in technology, business, and communication. Similarly, Uzbek incorporates new compound words in information technology, economics, and security. Some terms, like “smartphone” and “cybersecurity,” are present in both languages. The article concludes that language evolution reflects dynamic international interactions and will continue to integrate new terms.
Keywords: Lexical unit, compound words, technological development, uzbek language, language development, globalization, scientific progress / scientific development, technology, business, international cultural relations.